2023
DOI: 10.24996/ijs.2023.64.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Water Quality Using Water Quality Index and Heavy Metal Pollution Index: A Case Study of Al-Diwaniyah River, Iraq

Abstract: The current study aims to assess the water quality of the Al-Diwaniyah River in the city of Al-Diwaniyah to drink in terms of chemical properties and heavy metals and their impact on the health of the local population. The results showed that most of the parameters in the river water are of low concentrations due to the limited human activities in polluting the river water. The study concluded that the water quality is suitable for drinking depending on major cations and anions in all seasons. The Heavy Metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The highest concentration of heavy metals was recorded in well 1,2 by direct effect of oil and gas industry activity in this area, while in wells 23,30 were due to excessive use of fertilizer by farmers. During long time more 70 years ago especially this region are shallow groundwater table less than 30 m and high aquifer transmissivity [23]. The statistical analysis including the maximum value, minimum value, and average were tabulated for respective Heavy metals (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of heavy metals was recorded in well 1,2 by direct effect of oil and gas industry activity in this area, while in wells 23,30 were due to excessive use of fertilizer by farmers. During long time more 70 years ago especially this region are shallow groundwater table less than 30 m and high aquifer transmissivity [23]. The statistical analysis including the maximum value, minimum value, and average were tabulated for respective Heavy metals (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have confirmed the presence of some fungal species in river water sites and not in other sites, they can be considered as determinants of the presence of one of the elements (Nair et al, 2022). The concept of pollution stems from the principle of the presence of an unwanted substance in one of the systems, such as water, for example, the presence of a heavy metal in the water as a result of factory waste, etc which are thrown in Al-Diwaniyah River, which is 123 km long, and which has become one of the most important pollutants that the Diwaniyah River suffers from, as well as municipal waste (Al Asadi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%